Effects of zein-nisin edible coating on physicochemical and microbial load of 'Granny Smith' apple after long term storage. Issue 1 (31st December 2023) - Belay, Zinash A.; Mashele, Tinyiko G.; Botes, W. J.; Caleb, Oluwafemi James
ABSTRACT: "Granny Smith" apples are susceptible to quality deterioration and microbial decay during retail handling, and marketing display in plastic bags. Therefore, the effectiveness of coating as alternative packaging under retail condition was explored. Impact of edible coatings: zein, zein combined with nisin (zein-nisin) on maintaining various qualities microbial load on "Granny Smith" apples stored at 15°C for 21 days was investigated and compared with control samples. Results showed that weight loss (%) was highest in control samples (30%) by day 14, while zein edible coating significantly delayed weight loss till the end of storage day 21 ( p ≤ .05). Overall, changes in hue angle ( h° ), titratable acidity (TA), total soluble solids (TSS), and firmness were not significantly impacted by coating. However, the application of Zein-nisin coatings effectively resulted in 1.5 log and 3 log reduction by the end of storage day 21 in yeast and mould, and TAMB count, respectively.